Sistem Retensi dan Alih Image Rekam Medis Inaktif RS Khusus Kanker MRCCC Siloam Semanggi - Sudjiran, Sudjiran; Limbong, Akbar Syahbanta (Teknik Informatika Universitas Pamulang, 2021)
Along with the development of technology, the speed of data processing is needed in order to compete with competitors. A company must have an advantage over other companies if it does not want to lose in the competition. MRCCC Siloam Semanggi is a company that provides health services for cancer patients. One of the transaction processes within the hospital is sensing data in the form of images of patient data. Image data processing activities at this hospital are not yet structured and require a database in order to assist in fast data processing. This study aims to create an image transfer system to transfer physical documents into digital documents. This system is useful for hospital employees to be able to find documents easily for certain purposes, the system is made web-based using XAMPP, using PHP language with MySQL database. The results of the analysis of research that has been done, there are problems that arise related to the retention system in hospital patient data. Retention data collection activities are usually carried out by sorting out patient medical record documents from those not recorded on a computer.